2006
DOI: 10.1021/jf060482j
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferricin-Related Peptides with Inhibitory Effects on ACE-Dependent Vasoconstriction

Abstract: A selection of lactoferricin B (LfcinB)-related peptides with an angiotensin I-converting enzyme (ACE) inhibitory effect have been examined using in vitro and ex vivo functional assays. Peptides that were analyzed included a set of sequence-related antimicrobial hexapeptides previously reported and two representative LfcinB-derived peptides. In vitro assays using hippuryl-L-histidyl-L-leucine (HHL) and angiotensin I as substrates allowed us to select two hexapeptides, PACEI32 (Ac-RKWHFW-NH2) and PACEI34 (Ac-RK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
40
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 39 publications
11
40
0
Order By: Relevance
“…We have reported previously that angiotensin I induces ACE-dependent vasoconstriction in the rabbit isolated carotid artery, as supported by the inhibition of angiotensin I-induced but not angiotensin II-induced contractions by the ACE inhibitor captopril (Centeno et al, 2006). In the present study, challenge of rabbit carotid arterial segments with depolarizing solution (KCl 50 mM) induced phasic contraction followed by active tone maintained until KCl washout (Fig.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…We have reported previously that angiotensin I induces ACE-dependent vasoconstriction in the rabbit isolated carotid artery, as supported by the inhibition of angiotensin I-induced but not angiotensin II-induced contractions by the ACE inhibitor captopril (Centeno et al, 2006). In the present study, challenge of rabbit carotid arterial segments with depolarizing solution (KCl 50 mM) induced phasic contraction followed by active tone maintained until KCl washout (Fig.…”
Section: Resultssupporting
confidence: 85%
“…LFH was assayed in vitro for its capacity to inhibit the ACE activity using hippuryl-L-histidyl-L-leucine (HHL; Sigma) as substrate and following the protocol described previously (Centeno et al, 2006). ACE (from porcine kidney) was purchased from Sigma.…”
Section: In Vitro Assay Of Ace Inhibitory Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study showed that lactoferrin, a well known protein for its diverse biological activities including antimicrobial, antiviral and antioxidant activities (Tomita, Wakabayashi, Yamauchi, Teraguchi, & Hayasawa, 2002), possesses the most potent peptides in milk including VRW, with a predicted IC 50 value of 0.6 μM ( Table 2). Lactoferricin-related peptides were reported to have ACE inhibitory activity (Centeno et al, 2006). It should be noted that lactoferricinrelated peptides are rich in hydrophobic and positively charged amino acid residues, which were postulated to play an important role in the potency of ACE inhibitory peptides.…”
Section: Tablementioning
confidence: 99%
“…ACE catalyzes the release of the dipeptide His-Leu from the angiotensin I C terminus, which results in the octapeptide angiotensin II, a potent vasoconstrictor (45). ACE also hydrolyzes and inactivates the vasoactive bradykinin (4). Additionally, ACE is a stimulant for the release of aldosterone in the adrenal cortex (6,7).…”
mentioning
confidence: 99%